Impact of Moderate Exercise on Post-concussive Symptoms and Cognitive Function after Concussion in Children and Adolescents Compared to Healthy Controls - Anderson, Vicki; Manikas, Vicky; Babl, Franz E.; Hearps, Stephen; Dooley, Julian (International Journal of Sports Medicine, 2018)
Resolution of post-concussive symptoms (PCS) is a marker of recovery. However, it is unclear whether subtle impairments re-emerge in the context of increased demands. This study examined the effect of strenuous exercise on clinical symptoms and cognitive efficiency in children and adolescents after PCS resolution following concussion. We recruited concussed children and adolescents (n=30) on presentation to an Emergency Department (ED), and compared them to community-sourced non-injured controls (n=30), matched for age, and cognitive function. At Day 2 post symptom resolution, concussed participants (and controls) completed an exercise protocol, and pre- and post exercise assessments of PCS and computer-based cognitive efficiency. Findings demonstrated that, compared to controls, participants with recent concussion showed an overall reduction in PCS post-exercise (p=0.048), less impact of exercise on PCS than controls (p=0.021), and faster reaction times on computer-based cognitive tasks, even where cognitive demands were high (ps<0.05). These results provide preliminary support for the use of moderate exercise for the reduction of concussion post-symptom, as suggested in recent clinical guidelines.
Keywords: child; youth; concussion; recovery; exercise; cognition